Umbrella Monopole Antenna for 5G Applications - Lutfia, Paulen Aulia; Nurhayati, Nurhayati; Christydass, Samuel Prasad Jones (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
Umbrella Monopole Antenna (UMA) proposed in this paper for 5G application. We designed four models of UMA, i.e: UMA-A, UMA-B, UMA-C, and UMA-D. The antenna has a curvature in the patch as an umbrella shape with a feeding shape a microstrip feed line. Four variations of the patch antenna have been designed and get different performance in VSWR, surface current, and directivity. The proposed antenna has a wide bandwidth that operates 8 GHz â€“ 30 GHz with VSWR <2 dB. The Increasing of directivity is reached for UMA-A, UMA-C, UMA-D, and UMA-B, i.e: 6.38 dBi, 7.97 dBi, 8,84dBi, and 9,15 dBi respectively at 24 GHz.Â  The maximum gain has been reached for UMA-B of 9.15. The lowest frequency that has a return loss of 10 dB has resulted for UMA-D in the frequency around 5 GHz. All of the UMA antennas can be applied for 5G mmwave applications at 24 GHz and 28 GHz.